Functional relations of empathy and mentalizing: an fMRI study on the neural basis of cognitive empathy - Schnell, Knut; Drost, Sarah Maria; Konradt, Brigitte; Walter, Henrik (NeuroImage, 2011)
This fMRI study was set up to explore how cognitive empathy, i.e. the cognitive inference on another person's affective state, can be characterized as a distinct brain function relating to pre-existing neurofunctional concepts about mentalizing and empathy. In a 3 Tesla MRI scanner 28 healthy participants were presented with four different instructions randomly combined with 32 false-belief cartoon stories of 3 subsequent pictures free of direct cues for affective states, like e.g. facial expressions. Participants were instructed to judge affective or visuospatial changes from their own (1st person perspective) or the protagonists' (3rd person perspective, 3rdpp) perspective. 3rdpp-judgements about affective states differed from visuospatial 3rdpp judgements by a significantly higher activation of the anterior mentalizing network (dorsomedial prefrontal cortex, anterior superior temporal sulcus, temporal poles) and the limbic system (left amygdala and hippocampus). Analysis of main effects revealed that the anterior part of the mentalizing network was activated significantly stronger by affective compared to visuospatial content. In contrast, the temporoparietal junction was rather activated by 3rdpp visuospatial judgements. After all, our results demonstrate a functional dissociation between cognitive empathy and cognitive visuospatial perspective taking. The simultaneous activation of the cortical mentalizing network and the amygdala indicates that cognitive empathy actually involves reference to own affective states in the observer. Notably, the cognitive reference to own affective states activated the mentalizing network as well. Moreover our results support pre-existing ideas about a functional anterior-posterior subdivision of the mentalizing network, depending on affective content and 3rd person perspective of cognition.